Factors affecting the increasing population of students at the U.P. Institute of Library Science - Sabalburo, Jose Aldrin E.; Faderon, Rosalie B. (Quezon City : Institute of Library Science, University of the Philippines Diliman, 1999)
Library education in the Philippines has continuously experienced vast development and recognition. Together with this, LIS students have also continued to increase. This study is an investigation on the factors that affect the increasing population at the UPILS.
The UPILS has a total undergraduate population of 246 and all of the 96 students who were sent questionnaires responded. Of this number, 32 are shiftees, 32 are transferees, and 32 are BLS students since they first stepped into college. All of these students have almost the same personal characteristics and socio-economic status but the shiftees and transferees have different reasons for dropping their courses and each of the three student categories have different reasons for choosing the BLIS course at the UPILS.
The age distribution of the subjects ranged from seventeen (17) to twenty-four (24) years old. The median age of the group is 19.27. The size of the family of the respondents ranged from 3-12 members and most of them come from families having 3-4 (26.04 percent) and 5-6 (46.88 percent). Majority of the respondents belong to families with average and above-average economic status as judged from their annual family income which are mostly P 85,000 and above, and by the parents' occupations.
The two most highly rated reasons expressed by the shiftees in leaving while those of the transferees were "influenced by parents or other people" and "financial". Shiftees, transferees, and BLIS students who have been taking the course since their first year had different reasons for choosing the course. For the shiftees, it was due to disqualification from previous course; for the transferees, it was due to employment opportunities they foresee after graduating; and for the BLIS students since their freshman year, it was due to their own interest.
According to some of the full-time faculty of the Institute of Library Science, the developments in computer and information technology helped in the further development of the field of LIS and LIS professionals are finding new roles within their institutions and the society. Based on the findings and conclusions of this study, the UPILS should set up a more effective student recruitment program and produce brochures to be distributed to all graduating students in high school and freshmen attending library orientation programs to make them aware of the Bachelor of Library and Information Science course. Librarians and information specialists must do away with the stereotype image and project the new image of modern information professionals (MIPs). Even at the elementary school level, they must project their image to the young ones so that the latter will have a better understanding of their (MIPs) role in school and society. This will awaken in the students the desire to emulate the MIPs and motivate them to pursue a similar career.
Vita.
Computer print out.
Thesis (Bachelor of Library and Information Science)--University of the Philippines Diliman
Keywords: University of the Philippines Diliman. Institute of Library Science. Students